Isolation of endoxylanases from anaerobic bacterium Butyrivibrio sp. strain Mz5 is possible by anion exchange chromatography on CIM DEAE-8 monolythic column - Čepeljnik, Tadej (Acta chimica slovenica, 2002)
The xylanolitically active enzymes are of great interest for the industry and as feed additives as well. Therefore an effort was made to search for the microbial strains capable to degrade xylan. One of the most active rumen bacteria was Butyrivibrio sp. strain Mz5 possessing multiple xylanolytic enzyme system. In the present work the procedure for the separation of two of them is outlined. This was successfully done by anion exchange chromatography followed by gel filtration. Using the CIM DEAE tube was the key isolating point that prevented othewise frequent aggregation of the proteins and speededup the procedure. The isolated enzymes were of 51 and 58 kDa.
Keywords: bacteria; bakterije; Butyrivibrio; izolacija; kromatografija